Matrix Metalloproteinase Inhibitors as Anticancer Therapeutics - Mannello, F.; Tonti, G.; Papa, S. (Current Cancer Drug Targets, 2005)
Matrix metalloproteinases (MMPs), also designated as matrixins, play a central role in many biological processes and are involved both in physiologic cellular processes and in pathologic situations such as tumor growth, invasion and metastasis. For more than 30 years MMPs have been considered as promising targets for cancer therapy and a number of different synthetic and natural MMP inhibitors have been identified as cytostatic and anti-angiogenic agents and have begun clinical testing in view of their specific implication in malignant tissues. Although preclinical studies were so compelling to encourage several clinical trials, the past years have seen a consistent number of disappointments and limited success. The critical examination of previous studies shed light on new information about the cellular source, substrates and mode of action of MMPs, focusing the attention of future research on the identification of specific MMP targets in tumors at different stage of tumor progression, both in order to improve efficacy and to reduce the side effect profile. In this review we discuss the current view on the feasibility of MMPs as target for therapeutic intervention in cancer, taking into account that the perspective may be of great value for molecular medicine for the twenty-first century, providing intriguing information about the MMPs as mediators in biology and pathology, and as targets for disease therapies.
Keywords: therapeutic strategies